Beam energy and centrality dependence of two-pion Bose-Einstein correlations at SPS energies: CERES Collaboration - Adamová, Dagmar; Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Esumi, ShinIchi; Filimonov, Kirill; Glässel, Peter; Dubitzky, Wilrid; Milošević, Jovan; Petráček, Vojtech; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2002)
Results are presented of a two-pion interferometry (HBT) analysis in Pb+Au collisions at 40, 80, and 158 AGeV. A detailed study of the Bertsch-Pratt HBT radius parameters has been performed as function of the mean pair transverse momentum kt and in bins of the centrality of the collision. From these results we extract model-dependent information about the space-time evolution of the reaction. An investigation of the effective volume of the pion emitting system provides an important tool to study the properties of thermal pion freeze-out.